Economic crisis, quality of work, and social integration: the European experience (New York, 2013)
"The quality of working life has been central to the sociological agenda for several decades, and has also been increasingly salient as a policy issue, and for companies. This book breaks new ground in the study of the quality of work by providing the first rigorous comparative assessment of the way it has been affected by the economic crisis. It examines the implications of the crisis on developments in skills and training, employees' control over their jobs, and the pressure of work and job security. It also assesses how changing experiences at work affect people's lives outside of work: the risks of work-life conflict, the motivation to work, personal well-being, and attitudes towards society. The book draws on a rich new source of evidence--the European Social Survey-to provide a comparative view over the period 2004 to 2010. The survey provides evidence for countries across the different regions of Europe and allows for a detailed assessment of the view that institutional differences between European societies--in terms of styles of management, social partnership practices, and government policies--lead to very different levels of work quality and different experiences of the crisis. This comparative aspect will thus forward our understanding of how institutional differences between European societies affect work experiences and their implications for non-work life."